Assessment of required nodal yield in a high risk cohort undergoing extended pelvic lymphadenectomy in robotic‐assisted radical prostatectomy and its impact on functional outcomes. (23rd July 2012) - Sagalovich, Daniel; Calaway, Adam; Srivastava, Abhishek; Sooriakumaran, Prasanna; Tewari, Ashutosh K.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Although high risk prostate cancer patients are most vulnerable to lymph node invasion, the definition of an extended pelvic lymph node dissection (PLND) for this cohort has remained vague. Additionally, there have been compelling data in the rectal cancer literature relating erectile dysfunction to the extent of PLND. Because of the similarities of the dissection templates, we investigated the impact of an extended PLND on urinary and sexual function. In the present study, we were able to determine a minimal lymph node yield necessary for accurate staging of high risk patients. Expanding the analysis to our entire cohort, we found worse potency outcomes in patients with an extended PLND, demonstrating that extended PLND may be counterproductive to the aims of nerve sparing in a lower risk population. Objectives To establish a minimal lymph node yield (LNY) necessary for accurate staging in a high risk cohort, since no consensus exists as to the optimal extent of pelvic lymph node dissection (PLND) needed during radical prostatectomy in high risk patients. To investigate the impact of an extended PLND on urinary and sexual function. Patients and Methods In all, 760 men underwent robotic‐assisted radical prostatectomy from January 2010 to May 2011 by a single surgeon (AKT). Low and intermediate risk groups (as defined by the D'Amico classification) underwent a minimum of a limited PLND (obturator/external iliac packets) and high risk patients underwent an extended PLND (as limited plus hypogastric, triangle of Marcille and common iliac packets up to the level of the ureteric crossing). In order to analyse LNY for staging purposes, the high risk group (n = 82) was subdivided into patients with ≥13 LNY vs <13 LNY and the incidence of lymph node (LN) invasion was compared between these groups. To study the impact of extended PLND on functional outcomes, we evaluated patients from our total cohort who were preoperatively potent (Sexual Health Inventory for Men ≥17), continent and who received bilateral nerve‐sparing surgery. Return to potency at 26 weeks postoperatively was defined as a score of ≥3 on questions 2 and 3 of the Sexual Health Inventory for Men questionnaire, and continence was defined as zero pads per day or one pad for security per day. Results Median LNYs in the low, intermediate and high risk groups were (interquartile range [IQR]) 5 (2–10), 7 (3–12) and 13 (6–20) (P < 0.001); LN positivity was 0% (0 of 309), 0.8% (3 of 369) and 13.4% (11 of 82) in the three respective groups (P < 0.001). Median LNYs (IQR) among the high risk LN positive and negative patients were 20 (13–22) and 11 (5–18) (P = 0.05); 5% of the patients had positive LNs in the <13 LNY group vs 21% of patients in the >13 LNY group (P = 0.036). Median (IQR) console time was significantly different, at 120 min (95–137) for the ≥13 LNY group vs 100 min (85–120) for the <13 LNY group (P = 0.04). Among patients who fitted the inclusion criteria for functional outcomes (n = 561), 55.2% (16 of 29) with ≥20 LNs removed recovered potency at a median follow‐up of 6 months postoperatively vs 70% of patients with <20 LNs (301 of 430) (P = 0.020). There was no significant difference in continence recovery between the groups. Conclusions High risk patients should undergo an extended dissection with at least 13 LNs removed for accurate staging. Extended PLND with LNYs of ≥20 is associated with worse potency outcomes. With LN positivity occurring rarely in low risk patients, extended PLND may be of little oncological benefit but with significant functional compromise in this cohort.